Relationships between land-use intensity, woody species diversity, and carbon storage in an arid woodland ecosystem - Magnano, Andrea Laura (2023)
Forest ecosystems play a key role in providing multiple ecosystem services, such as carbon fixation and storage, but face pressures from human development that jeopardize their integrity and functioning. Accurately understanding the relationships between land use-intensity, biodiversity, and carbon storage is important for developing viable strategies to promote carbon sequestration. Here, we analyzed the effect of land-use intensity on the relationship between woody plant functional diversity and carbon storage in Prosopis woodlands of the central Monte desert of Argentina. We worked in sixteen 900 m2 square plots along disturbance gradients, eight located in highly disturbed woodlands close to livestock settlements and eight in slightly disturbed woodlands ca. 2 km away from settlements. We measured woody plant taxonomic and functional diversity and dominance metrics, and estimated carbon stocks in biomass, necromass and soil organic compartments. Our study shows that increasing land-use intensity erodes taxonomic and functional diversities and, ultimately, carbon storage. We found that lower carbon stocks around livestock settlements were driven by shrubs, trees, roots, litter, and dead plants, but were unaffected by the herb, woody debris, and soil compartments. Furthermore, positive relationships among woody species richness and functional trait diversity seem more important than the existence of few highly dominant species in determining carbon storage, providing stronger evidence for niche complementary than for mass ratio effects. We hope our study contributes to the understanding how livestock management practices influence carbon storage in Prosopis woodlands.